PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN SIKAP KERJA SAMA DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK DI SDN KENCANA INDAH II - Rahayu, Ika; Yulistiani, Irna (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2016)
The problem of this research is to increase cooperation attitude and student learning outcomes through the implementation model of Problem Based Learning on thematic learning themes subthemes 1 1 wonderful togetherness nation of cultural diversity in the class IV SDN Kencana Indah 2 Rancaekek District of Bandung regency. This study aims to determine the attitude of cooperation and improvement of student learning outcomes through the implementation model of Problem Based Learning in Scene 1 Indahnya Mutual Subtheme 1 Nation Cultural Diversity in Class IV. As the subjects in this study is the fourth grade students of SDN Kencana Indah 2 as a single class of 33 students. The research object of this class action is the improvement of the attitude of cooperation and student learning outcomes at 1 beauty togetherness theme of cultural diversity subtema one nation by using model Problem Based Learning. Implementation of a class action (PTK) was done 2 cycles and each cycle is done with 2 meetings and at the end of each cycle of observation to determine the result of increased cooperation attitude and student learning outcomes. The results of the research can be argued that the percentage of category cooperative attitude of students the observation of the first cycle of the first meeting included the category "Not Visible" reached 57.7%; category "Start Invisible" reached 72.7%; category "Start Developing" reached 39.4%; and the category "have been entrenched" reached 15.2%, while in the second cycle in the category "Not Visible" reached 15.2%; category "Start Invisible" reached 42.4%; category "Start Developing" reached 33.3%; and the category "have been entrenched" reached 93.9%. Besides the increase occurred in student learning outcomes of the first cycle that 45.5% to 84.8% in the second cycle. Thus it can be argued conclusion that the application of the model of Problem Based Learning can improve the attitude of cooperation and student learning outcomes in thematic learning themes subthemes 1 1 wonderful togetherness nation of cultural diversity in the class IV SDN Kencana Indah 2 Rancaekek District of Bandung regency.